2006
DOI: 10.1002/cncr.21632
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the 1992 and 2002 pathologic T3 substages for the prediction of biochemical recurrence after radical prostatectomy

Abstract: BACKGROUNDThe objective of this study was to compare the ability of the 1992 American Joint Committee on Cancer (AJCC) TNM staging system for nonorgan‐confined prostate carcinoma (PCa) (pathologic T3 [pT3a], pT3b,and pT3c) to predict biochemical recurrence (BCR) after radical prostatectomy with its revision from 1997/2002 (pT3a and pT3b).METHODSThe authors analyzed prospectively collected data from 971 consecutive patients with pT3 tumors who underwent radical prostatectomy alone at a single institution. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…We observed similar effects in an earlier analysis of vitamin D and prostate cancer progression [we reported and discussed this in detail in ref 36]. In a study comparing the predictive ability of the two systems for classifying prostate cancer, Gleason score has been reported to have higher predictive accuracy for biochemical recurrence compared with TNM staging [37]. Interestingly, in the meta-analysis of BMI and prostate cancer by MacInnes and English [4], the study which showed the largest effect of BMI on increased risk of more aggressive cancer was that which used Gleason grading; all other studies used TNM staging and their results were all compatible with no increased risk.…”
Section: Discussionsupporting
confidence: 81%
“…We observed similar effects in an earlier analysis of vitamin D and prostate cancer progression [we reported and discussed this in detail in ref 36]. In a study comparing the predictive ability of the two systems for classifying prostate cancer, Gleason score has been reported to have higher predictive accuracy for biochemical recurrence compared with TNM staging [37]. Interestingly, in the meta-analysis of BMI and prostate cancer by MacInnes and English [4], the study which showed the largest effect of BMI on increased risk of more aggressive cancer was that which used Gleason grading; all other studies used TNM staging and their results were all compatible with no increased risk.…”
Section: Discussionsupporting
confidence: 81%
“…Both Gleason score and TNM are accepted as valid and reliable measures of assessing the aggressiveness and extent of prostate cancer and for predicting pathologic characteristics (46). However, Gleason score was found to have higher predictive accuracy for biochemical recurrence compared with TNM staging system in a study of 971 advanced prostate cancer patients (47). In our study, we found little overlap between advanced prostate cancer cases defined by these two methods (see Table 1).…”
Section: Discussionmentioning
confidence: 47%
“…Additionally, the prognostic value was comparable to that of T3/T4 disease, a variable often considered when predicting risk for PSAR. 27,28 …”
Section: Commentmentioning
confidence: 99%